Color and color uniformity variation of Scots pine wood in the air-dry condition - Grekin, Mika (US, 2007)
Appearance has an important influence on people's impression and valuation of wood products. One of the major factors that affects the appearance of wooden surfaces made of pine is the simultaneous presence of sapwood and heartwood as these components can vary considerably in color, and large differences between them can affect value and end-uses. In this paper, the color of Scots pine wood in the air-dry condition is discussed in terms of CIE L*a*b* color parameters and calculated color uniformity parameters between heartwood and sapwood from samples collected from stands in five geographical regions in Finland and Sweden. The background of the differences in color parameters is also discussed. There were significant differences in color parameters between heartwood and sapwood; in addition, geographical origin and sampling height within a tree had significant effects on color of both heartwood and sapwood. Some differences were also found between regions and heights in the color uniformity parameters. However, concerning the practical applications, the results should be considered as indicative due to several departures from conventional practices.
Keywords: Pinus sylvestris; lineaariset sekamallit